Hubungan usia awal pemberian MP-ASI dengan kejadian diare di Desa Lubuk Palas Kec. Silau Laut Tahun 2021 - Eliza Bestari Sinaga; Fifi Ria Ningsih Safari (Jurnal Maternitas Kebidanan, 2021)
Complementary Foods for Mother's Milk (MP-ASI) are foods or drinks that contain nutrients, which are given to infants to meet their nutritional needs. MP-ASI is given along with breast milk from 6 months to 24 months. As babies get older, after babies are 6 months old, they are introduced to complementary foods to meet their nutritional needs. The impact of giving MP-ASI too early is more frequent constipation, diarrhea, constipation, cough, runny nose and fever, compared to babies who are only exclusively breastfed. This study aims to determine the relationship between early complementary feeding and the incidence of diarrhea in Lubuk Palas Village, Silau Laut District in 2021. This type of research was cross sectional with a correlational study design. The population in this study were all mothers who had babies 0-6 months who lived in Lubuk Palas Village, Silau Laut District in 2021, as many as 35 people, while the samples taken in the study were all mothers who had babies under 0-6 months as many as 35 people. The results showed that there was a relationship between the availability of clean water and healthy latrines with the incidence of diarrhea in children under five. There is a relationship between early age of complementary feeding and the incidence of diarrhea in Lubuk Palas Village, Silau Laut District in 2021. It is expected that mothers who have babies at an early age in Lubuk Palas Village, Silau Laut District, should try to give exclusive breastfeeding until the baby is 6 months old.